Stress contingent changes in Hog1 pathway architecture and regulation in Candida albicans. - Alison M Day; Min Cao; Alessandra da Silva Dantas; Olga Ianieva; Carmen Herrero-de-Dios; Alistair J P Brown; Janet Quinn (PLoS Pathogens)
The Hog1 stress-activated protein kinase (SAPK) is a key mediator of stress resistance and virulence in Candida albicans. Hog1 activation via phosphorylation of the canonical TGY motif is mediated by the Pbs2 MAPKK, which itself is activated by the Ssk2 MAPKKK. Although this three-tiered SAPK signalling module is well characterised, it is unclear how Hog1 activation is regulated in response to different stresses. Functioning upstream of the Ssk2 MAPKKK is a two-component related signal transduction system comprising three sensor histidine kinases, a phosphotransfer protein Ypd1, and a response regulator Ssk1. Here, we report that Ssk1 is a master regulator of the Hog1 SAPK that promotes stress resistance and Hog1 phosphorylation in response to diverse stresses, except high osmotic stress. Notably, we find Ssk1 regulates Hog1 in a two-component independent manner by functioning to promote interactions between the Ssk2 and Pbs2 kinases. We propose this function of Ssk1 is important to maintain a basal level of Hog1 phosphorylation which is necessary for oxidative stress, but not osmotic stress, mediated Hog1 activation. We find that osmotic stress triggers robust Pbs2 phosphorylation which drives its dissociation from Ssk2. In contrast, Pbs2 is not robustly phosphorylated following oxidative stress and the Ssk1-mediated Ssk2-Pbs2 interaction remains intact. Instead, oxidative stress-stimulated increases in phosphorylated Hog1 is dependent on the inhibition of protein tyrosine phosphatases that negatively regulate Hog1 coupled with the Ssk1-mediated promotion of basal Hog1 activity. Furthermore, we find that inhibition of protein tyrosine phosphatases is linked to the hydrogen peroxide induced oxidation of these negative regulators in a mechanism that is partly dependent on thioredoxin. Taken together these data reveal stress contingent changes in Hog1 pathway architecture and regulation and uncover a novel mode of action of the Ssk1 response regulator in SAPK regulation.